Restoring the Importance of Cereal-Grain Legume Mixtures in Low-Input Farming Systems - Księżak, Jerzy; Staniak, Mariola; Stalenga, Jarosław (Agriculture (Basel), 2023)
In the paper, we overview the benefits of cereal-grain legume mixtures in low-input farming systems and identify the key factors affecting their agricultural performance. The review was based on the data collected from databases such as Google Scholar, Web of Science, and ScienceDirect. The gathered literature covered the original research articles, reviews, book chapters, and, in a few cases, conference proceedings. The focus was on literature coming from Mediterranean countries and Central-Eastern Europe, especially from Poland. Originating from two different plant families, legumes and cereals complement each other. The legumes provide biologically fixed nitrogen for the cereals in the mixture, but also increase its pool available to the following crops. Additional benefits include, but are not limited to more efficient pathogen and weed control, supply of high-quality fodder, and improved economic efficiency. Cultivation of crops after such mixtures usually results in higher and more stable yields. The productivity of cereal-grain legume mixtures largely depends on the soil factors (soil type, pH, water availability, etc.), crop species, crop variety, and crop management. Cereal-grain legume mixtures are particularly relevant to the poor (sandy) soils which are often unsuitable for the production of the components grown as a sole crop and are often linked with low-input farming systems.